PENGARUH TUNJANGAN KINERJA (TUKIN) DAN MOTIVASI TERHADAP KINERJA PEGAWAI POLITEKNIK KELAUTAN DAN PERIKANAN SORONG - Saharuddin, Saharuddin; Watunglawar, B.; Tafalas, Muhammad Guzali (Jurnal Noken: Ilmu-Ilmu Sosial, 2020)
The Purpose of this research is to process, analyze, prove empirically and discuss: (a) the effect of perfrormance benefits on the performance of Sorong Maritime and Fisheries Polythecnic employess; (b) The influence of motivation on the performance of Sorong Polytechnic Maritime and Fisheries employess; and (c) The join effect of performance and motivation allowance on the performance of Sorong Polytechnic Maritime and Fisheries employees. This research was conducted in September to November 2018. The author collected data through questionnaires and observation for a month. The population in this study is the Polytechnic Maritime and Fisheries totaling 66 people. This study is a study of facts in the form of opinions/opinion, attitudes, experiences or characteristics of people (respondents) as subject data in the form of primary data obtained from interviews, questionnaire and observation, also seconday data. Analysis of research data using descriptive statistics, with a view to finding strong relationship between variables through correlation analysis with regression analysis, by making comparisons by comparing the average sampel data or population. The results showed that (1) Performance allowance (X1) with all the components of its formation had no effect on employee performance (Y), so the first hypothesis stating that performance allowance (X1) affected employee performance (Y) was not proven; (2) Motivation (X2) with all the components of its formation affect employee performance (Y), so the first hypothesis stating that Motivation (X2) influences employee performance (Y) is proven. Â 